EFEKTIVITAS KOMPATIBILISER LLDPE-g-AO DALAM CAMPURAN POLI ASAM LAKTAT (PLA)/LINEAR LOW-DENSITY POLYETHYLENE (LLDPE) TERHADAP SIFAT FISIS DAN MEKANIS - Nengsi Handayanti Gaho; Ahmad Hafizullah Ritonga (PROSIDING SEMINAR KIMIA, 2022)
Semi-biodegradable plastic is an alternative that is currently being developed in order to reduce environmental pollution due to excessive use of commercial plastics and produce plastics that have physical and mechanical capabilities that are almost the same (not much different) with commercial plastics. However, the problem that arises is the low compatibility of mixtures with different polarities on the physical and mechanical strength of semi-biodegradable plastics. This study aims to determine the effectiveness of the addition of a linear low-density polyethylene grafting oleic acid (LLDPE-g-AO) compatibility to a mixture of poly lactic acid (PLA) and linear low-density polyethylene (LLDPE) in terms of physical and mechanical properties tests. The mixing of PLA and LLDPE was carried out through a blending method with a solvent system, where PLA used chloroform, LLDPE and the LLDPE-g-AO compatibilizer used xylene, which was followed by the addition of 1% glycerol in the mixing of the two resulting solutions. The results of this study indicate that the addition of LLDPE-g-AO effectively resulted in an increase in the mechanical strength and water absorption of the PLA/LLDPE mixture. The results of testing the mechanical properties of the most optimum tensile strength is the mixture of PLA/LLDPE/LLDPE-g-AO (70:22.5:7.5) which is 3.8078 MPa with the results of the physical properties test for absorption of 3.66 %. Keywords: PLA, LLDPE, LLDPE-g-AO, tensile strength, water adsorption